Distribution and genetic diversity of porcine hokovirus in wild boars - Cadar, Dániel; Cságola, Attila; Lőrincz, Márta; Tombácz, Kata; Spînu, Marina; Tuboly, Tamás (Archives of virology, 2011)
Porcine hokovirus (PHoV), a newly discovered member of the family Parvoviridae and the proposed genus Hokovirus, is considered phylogenetically distinct from other parvoviruses. Here, we report a comprehensive spatio-temporal study of PHoV infection in Romanian wild boars. The prevalence of PHoV differed significantly in samples from 2006/2007 (22.76%) and 2010/2011 (50.54%), and also increased with age. Sequence analysis of PHoVs from 2006/2007 showed a close relationship to PHoVs from pigs from England and wild boars from Germany, while the PHoVs from 2010/2011 were mostly similar to isolates from Hong Kong. The most variable regions were detected in the NS1 gene and proved to be suitable for analysis of the genetic diversity of the virus. It was observed that PHoVs from older wild boar samples differed from those collected recently. These results suggested that porcine hokovirus could be a newly emerging virus of both domestic and wild pigs with yet unknown implications.